The Pushkin Handbook - Bethea, David M., 1948- (Book collections on Project MUSE., 2005)
"From its beginnings Pushkin's oeuvre has accommodated numerous, often competing readings (of which the major trends are discussed in David Bethea's introduction). The Pushkin Handbook - containing arguments whose wellsprings lie in a range of intellectual traditions, including structuralism, prosody, Bakhtin, Orientalist studies, musicology, and more - if further testimony to the continuing complexity of Russia's preeminent writer."--Jacket.